The gender dimensions of sexual violence against migrant domestic workers in post-2019 Lebanon - Diab, Jasmin Lilian; Yimer, Banchi; Birhanu, Tsigereda; Kitoko, Ariane; Gidey, Amira; Ankrah, Francisca (Frontiers in Sociology, 2023)
Introduction In December 2020, the Lebanese Parliament passed the landmark Law 205 against sexual harassment that could see perpetrators spend up to four years in prison and pay fines up to fifty times the minimum wage. The law additionally affords protection to both the victims and any witnesses who testify against the accused. While the law was applauded as a step forward for sexual harassment victims, it excludes an important faction of the community—migrant domestic workers. The law falls short of international standards by addressing sexual harassment solely as a crime and neglecting to complement this law with labor law reforms, monitoring, and civil remedies. This research focuses on the various forms of sexual violence either protected or enabled under the Kafala system. It aims to depict the incessant violations this type of system has produced. Methods Qualitative interviews were conducted with 913 migrant domestic workers in Lebanon. A variety of multifaceted, mixed design methods were used to collect information during the write up of this report, all of which are participatory, inclusive and target group sensitive where needed. These methods ensured that the findings were derived from a collective contribution from a wide range of target groups, triangulated and validated, and that gender considerations were integrated into the data collection and analysis methods. Primarily, these methods included: (1) Desk/Policy Review; and (2) in-depth Key Informant Interviews. Results Whilst asked about whether or not they had survived at least one incident of sexual harassment during their employment or stay in Lebanon, 68% of respondents informed the study that they had. According to respondents, various forms of sexual harassment included: (1) inappropriate staring or leering in a sexual manner; (2) sexually suggestive comments/jokes/name-calling; (3) intrusive questions about your sex life/physical appearance that were offensive; (4) someone showing his/her private parts/half or fully-naked body offensively; (5) unwelcome touching, hugging, kissing or other inappropriate physical contact; (6) sexually explicit calls or messages; (7) repeated or inappropriate invitations to dates; (8) sexually explicit pictures, posters or other material; (9) actual or attempted rape or sexual assault; (10) video/photo taking of survivors of a sexual nature; (11) requests or pressure for sex or other sexual acts; and/or (12) other forms of sexual harassment. 56.2% of the sample (513 women) insisted that they had experienced at least one of the aforementioned forms of sexual assault, while 11.7% (107 women) confirmed that they had experienced sexual assault, but weren't willing to describe their experiences in detail. Discussion The variety in nationality and race across the sample presented important findings pertaining to ill-treatment, fetishization, and violence each group of women faced. In addition to an overall sense of racism experienced by black MDWs, hierarchy within the MDWs' community presents itself in various forms-even at the early stages of recruitment at the agency. Undocumented MDWs are left powerless in terms of reporting sexual abuse and therefore, are at the mercy of the aggressor. Navigating the country's legal, cultural and social landscapes without documentation or a legal residency permit has become increasingly difficult in recent years, as this has laid the foundation for exploitation and abuse in the areas of: (1) paying less than what MDWs deserve; (2) taking advantage of their legal standing to make them work longer hours; (3) threatening to report them to the authorities if they object; and (4) sexual harassment in all forms.